PROBLEMS OF RAISING THE LEGAL CULTURE OF YOUNG PEOPLE DURING THE FORMATION OF CIVIL SOCIETY - Abdullayev A’zam Abdievich (Web of Journals Publishing, 2023)
The article theoretically and practically analyzes that the increase in social activity of young people is a factor of development in the development of civil society, the modern socio-philosophical aspects of the concept of civil society from a methodological point of view, as well as the laws of increasing social activity of young people in the development of civil society, to show the place of innovative ideas in this process and tried to give practical instructions.
Keywords: civil society, democratic society, law, legal state, legal consciousness, legal culture, social consciousness, personality education.